The risk and obstetric outcomes of preeclampsia in pregnancies with non-ideal maternal age: a systematic review - Azizah; Wijayanti , Siwi Pramatama Mars; Rejeki, Dwi Sarwani Sri (Poltekkes Kemenkes Yogyakarta, 2025)
Preeclampsia remains a leading cause of maternal and neonatal morbidity, with increased risk observed at both extremes of maternal age adolescents (<20 years) and women of advanced maternal age (>35 years). However, the comparative obstetric impacts of preeclampsia across these age groups remain underexplored in a structured synthesis. This study aims to provide an up-to-date, evidence-based understanding to support maternal health policy planning, clinical obstetrics, and reproductive education tailored to high-risk populations. This systematic review was conducted following PRISMA guidelines. Electronic databases including PubMed, Scopus, and Google Scholar were searched for peer-reviewed studies published between 2015 and 2025. Studies were eligible if they reported preeclampsia prevalence and obstetric outcomes among pregnant individuals aged <20 or >35 years. Seven observational and cohort studies met the inclusion criteria. Adolescent pregnancies complicated by preeclampsia showed high cesarean section rates (82.9% in those aged ?16 and 89.3% in ages 17–19), and increased risk of anemia and pregnancy complications despite comparable neonatal outcomes across age subgroups. In contrast, advanced maternal age was associated with a higher prevalence of severe preeclampsia (68.9%), eclampsia (12.3%), HELLP syndrome (8.7%), and emergency cesarean delivery (71.3%). Neonatal complications included low birth weight (34.4%) and lower five-minute Apgar scores. Use of assisted reproductive technologies in women ?40 further amplified the risk of early-onset preeclampsia and prematurity. Pregnancies at non-ideal maternal ages carry distinct pathophysiological risks and result in increased obstetric complexity and need for medical intervention. Age-specific clinical approaches such as early screening, targeted antenatal education, and enhanced maternal-fetal surveillance are essential. These findings support maternal health policies that incorporate maternal age as a key determinant for individualized risk assessment and care planning.